2014
DOI: 10.1039/c4ra00645c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental connections between aqueous–aqueous and aqueous–ionic liquid biphasic systems

Abstract: Aqueous-ionic liquid (A-IL) biphasic systems containing deuterated water, deuterated nitric acid (10 À2 M to 7 M) and either [C 1 C 4 im + ][Tf 2 N À ], [C 1 C 10 im + ][Tf 2 N À ] or [Me 3 BuN + ][Tf 2 N À ] have been examined in terms of water and acid solubilities in the IL-rich phase and in terms of IL cation and anion solubilities in the waterrich phase. Other experiments focused on the IL cation and anion solubility in the water-rich phase upon addition of either [C 1 C 4 im + ][Cl À ] or [Li + ][Tf 2 N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 49 publications
(96 citation statements)
references
References 53 publications
10
86
0
Order By: Relevance
“…[32] In our previous work, [29] our model was built on the assumption that the concentrationso fb oth [Tf 2 N À ]a nd [C 4 mim + ]i ons, which intervene in the two extraction equilibria shown in Equations (3) and (4), N À ]v ariations are strongly dependento nb othT BP and nitric acid concentrations, and that the RTIL cation and anion behave in adifferent way.W e, thus, need to take this fact into accounti no ur new model.Considering the intricate ion exchanges in such biphasic systems, [31,33] we limit ourselves to an empiricalm athematicald escription of the concentration data, by use of ad hoc analytical expressions between [HNO 3 ] = 0a nd 7 m as Equations (7) and (8):…”
Section: Extraction Data Modelling and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[32] In our previous work, [29] our model was built on the assumption that the concentrationso fb oth [Tf 2 N À ]a nd [C 4 mim + ]i ons, which intervene in the two extraction equilibria shown in Equations (3) and (4), N À ]v ariations are strongly dependento nb othT BP and nitric acid concentrations, and that the RTIL cation and anion behave in adifferent way.W e, thus, need to take this fact into accounti no ur new model.Considering the intricate ion exchanges in such biphasic systems, [31,33] we limit ourselves to an empiricalm athematicald escription of the concentration data, by use of ad hoc analytical expressions between [HNO 3 ] = 0a nd 7 m as Equations (7) and (8):…”
Section: Extraction Data Modelling and Discussionmentioning
confidence: 99%
“…[31] Those data are compared in Figure 1w ith those obtained by contacting the same aqueous phases with aT BP/RTIL phase ([TBP] = All these data werea cquired in the absence of U VI .A lthough some researchers have shown that large amounts of metal may influence the distribution of all compoundsi nb iphasic systems, [40] we consider our data to be applicable to Ue xtraction, because Uranium distribution coefficients (D U )v alues are identical from U = 10 À2 m down to trace amounts. [25,29] As am atter of fact, our uranyl extraction data published previously [29] were obtained for [UO 2 2 + ] eq,ini = 10 À3 m,w hereas the characterization of extracted species had to be acquired at higher uranium concentrations ([UO 2 2 + ] eq,ini = 10 À3 m), owing to the detectionl imits.…”
Section: Effect Of Tbp In the Rtil Phase On The Solubility Of Rtil Iomentioning
confidence: 97%
See 3 more Smart Citations